2017
DOI: 10.1039/c6ob02618d
|View full text |Cite
|
Sign up to set email alerts
|

Stereodynamics and edge-to-face CH–π aromatic interactions in imino compounds containing heterocyclic rings

Abstract: By comparison with close contact interactions between benzene rings there is a paucity of experimental data available for attractive interactions involving aromatic heterocyclic rings, especially for small molecules in solution. Herein we describe aromatic heterocyclic and carbocyclic edge-to face interactions and conformational stereodynamics of N-1,2-diphenylethyl imines bearing a phenyl group and either a 2-pyridyl, 3-pyridyl, 2-thiophene or 2-furanyl moiety on the imino carbon. X-ray crystal structures hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…Attractive edge-to-face interactions are also found between phenyl rings of TDO (Phe-216) and of substrates 1g (Figure 2A) and 1k (Figure 3B). Edge-to-face interactions, between phenyl and thienyl groups, were earlier identified by NMR and X-ray crystallographic studies of imines [80]. Similar novel edge-to-face interactions are observed between phenyl (Phe-216) and thienyl rings in substrates 1a (Figure 1A,B), 1g (Figure 2A,B), 1k (Figure 3A-C).…”
Section: Molecular Docking Of 3-phenylthiophene 1k At the Tdo Active Sitesupporting
confidence: 75%
“…Attractive edge-to-face interactions are also found between phenyl rings of TDO (Phe-216) and of substrates 1g (Figure 2A) and 1k (Figure 3B). Edge-to-face interactions, between phenyl and thienyl groups, were earlier identified by NMR and X-ray crystallographic studies of imines [80]. Similar novel edge-to-face interactions are observed between phenyl (Phe-216) and thienyl rings in substrates 1a (Figure 1A,B), 1g (Figure 2A,B), 1k (Figure 3A-C).…”
Section: Molecular Docking Of 3-phenylthiophene 1k At the Tdo Active Sitesupporting
confidence: 75%
“…Previous docking studies of arene substrates with TDO indicated that the preferred orientations were controlled by: (i) attractive edge-toface T shaped interactions with the orthogonal phenyl group of Phe-216 and imidazole ring of His 222 and (ii) Van der Waals interactions with the proximate hydrophobic amino acids Ile-276, Leu-272, Ile-324, Val-309, Leu-272, Phe-352 (Hoering et al, 2016;Vila et al, 2016aVila et al, ,b, 2017Boyd et al, 2017Boyd et al, , 2019. Theoretical, crystallographic and experimental support for phenyl-phenyl and phenyl-pyridyl edge-to-face bonding (Tbonding) interactions, between arene and heteroarene rings, has been reported (Jennings et al, 2001;Escudero et al, 2009;Gonzalez-Rosende et al, 2017;Aliev and Motherwell, 2019). Little evidence was available, from crystalline protein structures, for similar edge-to-face interactions between the imidazole ring of histidine with other aromatic residues, e.g., Phe, Tyr, Trp, His (Bhattacharyya et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Edge‐to face interactions between phenyl rings have been widely reported in reviews, but much less information is available on similar interactions between phenyl groups and five membered heterocyclic rings . Recently, evidence for the edge‐ to‐face interactions between benzene and furan or thiophene rings has been reported . To date little evidence for edge‐to‐face bonding between benzene and imidazole rings appears to have been been reported.…”
Section: Resultsmentioning
confidence: 99%